Psychometric properties of the self-assessed wisdom scale among Turkish senior nursing students - Sema Kaymak; Seher Basaran-Acil; Sergul Duygulu (BMC Nursing)
Abstract Aim To adapt the Self-Assessed Wisdom Scale (SAWS) into Turkish and to conduct a validity and reliability study with senior nursing students. Methods This study was methodological research. Translation and back translation methods were used to translate the scale into Turkish. Seven experts’ opinions in nursing field were consulted for content validity. The study was conducted with 306 senior nursing students. Data were collected using Student Information Form and SAWS. Confirmatory factor analysis and structural equation modeling were used for construct validity. Cronbach’s alpha value, test-retest method, and Pearson correlation coefficient were used for reliability analysis. Results After ensuring language equivalence, the content validity was performed. The content validity index of the scale was 0.95. The items’ content validity index (CVIs) ranged between 0.83 and 0.98. The Turkish version of the SAWS (SAWS-TR) has 37 items, and five factors. The 16th, 39th, and 40th items were removed from the original scale due to their low factor loadings. The results CFA were; χ2/df 2.461, RMSEA 0.069, GFI 0.803, CFI 0.807, TLI 0.801, IFI 0.806, and SRMR 0.098. The total Cronbach’s alpha value of the scale was 0.91 and the sub-dimension Cronbach’s alpha values ranged between 0.78 and 0.85. Test-retest was performed one week apart and there is a statistically significant difference between the test-retest results of the scale (r = 0.668, p > 0.05). These results show that the SAWS-TR measures the same variable at different times at acceptable level. Conclusions The 37-item SAWS-TR is a valid and reliable tool that can be used to evaluate wisdom among Turkish senior nursing students. Nurse educators can utilize the SAWS-TR instrument to assess the wisdom of nursing students, thereby facilitating the development of their decision-making competencies during clinical practice.